(untitled) (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2022)
Deprivation of the compulsory portion in favor of the descendants in order to be valid, it is necessary to accomplish certain conditions. Such a valid deprivation from their side more to cause certain consequences. Thus, in the paper we study the conditions for the valid deprivation of the compulsory portion and the caused consequences. This of course from their side leads to the elaboration of certain theoretical dilemmas. In this regard it is especially important question whether the deprivation of the descendant in the will should state in whose favor the deprivation is, that is, that deprivation is in favor of the descendants. Also eam of attention is the question when there is a deprivation of the compulsory share in favor of the descendants, whether the deprived descendant is considered to have died before the testator or not? This is certainly important for which persons are called to inherit, ie which descendants will inherit that part of the inheritance. Namely, the aim of the paper is to study the conditions for deprivation, the consequences of such deprivation, theoretical dilemmas, with appropriate application of comparative solutions.